Mineral dust exposure in young Indian adults: an effect on lung growth?. Issue 5 (23rd May 2007) - Green, D A; McAlpine, G; Semple, S; Cowie, H; Seaton, A
Abstract : Background/objective: Long-term occupational exposure to mineral dusts including quartz is known to cause pneumoconiosis but little is known about the effects of such exposure during the period of lung development in childhood. The objective of this study was to investigate the effects on young people of exposure to mineral dusts. Methods: We carried out a cross-sectional study of a group of 81 Indian stone crushers (average age 21) and a control group of 72 nearby slum dwellers (average age 21) in order to assess dust exposures, respiratory symptoms and lung function. Results: Stone crushers' corrected 8-hour time weighted average concentrations of total inhalable dust, respirable dust and respirable crystalline silica were 143 mg/m 3, 39.7 mg/m 3 and 2.29 mg/m 3 respectively, which are 14, 10 and 23 times the UK workplace exposure limits, respectively. Both groups also had high exposures to outdoor and general domestic particulate matter. Compared to controls, stone crushers had significantly more symptoms, lower levels of forced vital capacity (FVC) and forced expiratory time (FET) and higher levels of forced expiratory volume in one second (FEV1 )/FVC ratio and mid-expiratory flow rate (MEF). There were no differences in FEV1 levels. Symptoms and lung function were not associated with time lived on site or time spent in job. A selection of chest radiographs showed no silicosis by International Labour Office (ILO) criteria. Conclusion: Individuals exposed to mixed mineral dust in childhood and early adult life had excess symptoms and reduced vital capacity without airflow obstruction compared with control subjects. We interpret this as evidence of stunting of lung growth caused by exposure to respirable dust.